A practical proposal for utilisation of water hyacinth: Recycling in fired bricks. (20th July 2018) - Goel, Gaurav; Kalamdhad, Ajay S.
Abstract: Strenuous efforts are being made to make the manufacturing activities sustainable. Consequently, industries are seeking ways not only to reduce energy consumption, waste accumulation and carbon footprint but also to reduce exploitation of precious natural resources. Fertile soil is one such precious resource which is being used for brick manufacturing for centuries. Brick industry needs frugal innovations to accommodate large quantities of waste and to make the production processes sustainable. Numerous studies in the past have tried to recycle waste materials by incorporating them into the brick production cycle. This experimental feasibility study is first to demonstrate the use of aquatic weed (water hyacinth) in brick manufacturing. Using chemical-mineralogical and physical-mechanical characterization, optimal mixing ratio of water hyacinth (WH) and soil was determined for achieving the desirable mechanical properties (compressive strength and water absorption) of a fired clay brick compliant with Indian and ASTM standard codes. XRD results confirmed that addition of WH does not cause compositional changes in the phase and leads merely to an increased porosity in bricks. An optimum mix of 10% WH with soil and a firing temperature of 900 °C were found appropriate for brick production using WH as a partial substitute to the soil. Greenhouse gas (CO2 ) emission during firing was ascertained and it was estimated that incorporation of 10% WH leads to 7% net saving in the consumption of external fuel required for firing the bricks. Highlights: Fired bricks containing water hyacinth (WH) were produced. Mechanical and durability properties of bricks incorporating WH were studied. Saving in energy consumption for firing of WH incorporated bricks was evaluated. Addition of WH in brick manufacturing can lead towards sustainable and cost effective construction.